2013
DOI: 10.1111/ger.12028
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Relationships between glandular salivary flow rates and dental caries

Abstract: Objective This study was designed to evaluate the relationship of age, gender, ethnicity and salivary flow rates on dental caries in an adult population using data collected from the Oral Health San Antonio Longitudinal Study of Aging (OH:SALSA). Background Saliva is essential to maintain a healthy oral environment and diminished output can result in dental caries. Although gender and age play a role in the quantity of saliva, little is known about the interaction of age, gender and ethnicity on dental carie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
8
1
Order By: Relevance
“…This result is in agreement with previous studies [37,38]. On contrast, other studies found that lower salivary flow rates play a significant role in caries development [39,40].…”
Section: Discussionsupporting
confidence: 94%
“…This result is in agreement with previous studies [37,38]. On contrast, other studies found that lower salivary flow rates play a significant role in caries development [39,40].…”
Section: Discussionsupporting
confidence: 94%
“…Individuals with high skill occupations are usually placed in psychologically stressful circumstances, which can cause a decrease in salivary flow 23 , 24 ) . Thus, reduced salivary flow in turn contribute to the development of dental caries 25 , 26 ) . According to the previous report, individuals with higher levels of academic stress had greater risks of developing dental caries 27 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The disease is characterized by lymphocytic infiltration of exocrine tissues along with salivary and lacrimal hypofunction [6, 7]. Loss of salivary flow results in patient discomfort, tooth decay, and difficulty in speaking and eating [8, 9]. Patients may also experience keratoconjunctivitis sicca or inflammation of the eyes as a result of dryness that often leads to ocular discomfort and impaired vision [10].…”
Section: Introductionmentioning
confidence: 99%